(untitled) (Fiep Bulletin - online, 2014)
This investigation has the physical activity and the health at schools as a main theme. The objective is to analise the theoretical and methodological ways that physical education classes are being developed to understand if such practices are promoting attitudes to see the physical activity as privileged element for health and life quality. This study establishes as important aim to valorize the physical activity and health as important themes for the critical formation of the students at school, and an important way to improve the students life’ quality. For theoretical supports some important authors as Daólio, Betti, Guedes & Guedes are referenced to make critical analyses of the theme possible. As results, we verified that the theory still, aided in paradigms that fragment the human being and doesn’t see it as a totality. The bodies comprehension needs to be changed to consider it as subject, in search of autonomy, conscience of itself, the world and the others bodies. We conclude that the incorporation of a solid theoretical production on the theme is necessary for the teachers because it will contribute to help them to understand physical activity and the health as privileged contents in the students’ formation process and for the improvement of their life quality.